Endgame : inside the Royal Family and the Monarchy 's fight for survival - Scobie, Omid (Dey Street Books, an imprint of William Morrow, 2023)
"On September 8, 2022, the world stood still as news broke of Queen Elizabeth II's passing. Her death dismantled the protective shield around the world's most famous family and saw a long-simmering crisis of confidence in the British monarchy begin to resurface. Now, with unique insight, deep access, and exclusive revelations, journalist Omid Scobie pulls back the curtain on an institution in turmoil, exposing the infighting, family deterioration, and outdated practices threatening its very future. This is the monarchy's endgame. Do they have what it takes to save it?